Effects of urbanization, biotic and abiotic factors on aquatic insect diversity in urban ponds - Keinath, Silvia; Onandia, Gabriela; Griesbaum, Frederic; Rödel, Mark-Oliver (Frontiers in Ecology and Evolution, 2023)
Urbanization leads to drastic modifications of the terrestrial and aquatic environment. However, urban ponds may provide valuable habitats for different taxa, including aquatic insects and amphibians. We aim to understand how a set of biotic and abiotic factors influence aquatic insect diversity in 18 urban ponds in the German metropolis Berlin, one of the greenest whilst most densely populated European cities. Greenspace is important for the terrestrial stages of some aquatic insects and amphibians, providing crucial resources. Thus, greenspace was assumed to have positive effects on aquatic insect diversity, whereas built-up area was assumed to affect diversity negatively. Because some aquatic insects prey on tadpoles, their abundance and diversity were assumed to depend on tadpole abundance, which in turn, depends on other food (i.e., phytoplankton) availability in ponds. We visited the ponds twice a year, in spring and summer, and collected data on aquatic insects that are known to prey on tadpoles, tadpole abundance, phytoplankton biomass, the presence or absence of large insect predators, as well as physical–chemical parameters. We assumed higher total aquatic insect abundance, genera richness, alpha-diversity, and evenness, as well as abundance and genera richness of different aquatic insect taxonomic groups to be associated with high tadpole abundance in ponds surrounded by high amount of greenspace and low levels of built-up area. Accordingly, we expected aquatic insects to be modulated by phytoplankton biomass, the presence of newts and fish, and to be affected by ponds’ abiotic conditions. Our results showed that biological interactions and abiotic water conditions override urban effects in ponds’ terrestrial surroundings on aquatic insect diversity levels, whereas aquatic insects’ taxonomic groups responded differently on different land-use types around ponds. We explain our findings due to different dependences and demands towards terrestrial and/or aquatic habitats by different taxonomic groups of aquatic insects, and differences in their colonization behavior.